CircHIPK3 Plays Vital Roles in Cardiovascular Disease - Zhang, Lei; Wang, Yin; Yu, Fei; Li, Xin; Gao, Huijuan; Li, Peifeng (Frontiers in Cardiovascular Medicine, 2021)
Circular RNAs (circRNAs) are covalently closed RNAs that function in various physiological and pathological processes. CircRNAs are widely involved in the development of cardiovascular disease (CVD), one of the leading causes of morbidity and mortality worldwide. CircHIPK3 is generated from the second exon of the HIPK3 gene, a corepressor of homeodomain transcription factors. As an exonic circRNA (ecRNA), circHIPK3 is produced through intron-pairing driven circularization facilitated by Alu elements. In the past 5 years, a growing number of studies have revealed the multifunctional roles of circHIPK3 in different diseases, such as cancer and CVD. CircHIPK3 mainly participates in CVD pathogenesis through interacting with miRNAs. This paper summarizes the current literature on the biogenesis and functions of circHIPK3, elucidates the role of circHIPK3 in different CVD patterns, and explores future perspectives.